ANALISIS KORELASI PENINGKATAN KAPASITAS PENJUALAN TERHADAP KUALITAS PRODUK, HARGA DAN PROMOSI PADA TOKO BAHAN KUE LESTARI BATAM - Mulyadi; Albertus Laurensius Setyabudhi (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
The study was made to determine the correlation of the factors that influence the increase in sales capacity of the Lestari cake ingredient shop which sells cakes and cake ingredients in Batam City. The company is run by a family and is engaged in the business of making bread and also marketing it. Challenges are always there, with cafes & bakeries already having brands and interests. Of course, the challenges are difficult and a problem for business people. This study uses quantitative methods to obtain the relationship between variables and to test existing hypotheses using samples obtained from the existing population. The preparation of the data was taken by means of observation, question and answer and questionnaires. The sample in the study was 98 people. The questions posed to the entire sample amounted to 20 questions. The report uses three free variables and one bound variable, so that each variable can have 5 questions asked. Of all the questions that exist, all of them are declared valid. From the results of the analysis test between Product Quality (X1), Price (X2), Promotion (X3) variables in sales capacity (Y), it can be explained that among the three independent variables, the one that has more influence on sales capacity is the product, namely 55, 60% has an effect on increasing sales capacity.